DFT Study of lewis base interactions with the MgCl2 surface in the ziegler-natta catalytic system: expanding the role of the donors - Vanka, Kumar; Singh, Gurmeet; Iyer, Divya; Gupta, Virendra K. (Journal of Physical Chemistry C, 2010)
We present a computational study, using density functional theory, of the role of internal and external donors in supported heterogeneous Ziegler-Natta polymerization catalyst systems. The focus of the investigation is the ability of the donors to stabilize the MgCl2 support through the zip mode of coordination. Phthalates and alkoxy benzoates have been considered as representative internal and external donors, respectively. Models for the alpha (ccp) and the beta (hcp) phases of the (110) MgCl2 lateral cut have been considered. Studies were first done with a ``Fully Fixed Model'', where the atoms in the MgCl2 lateral cuts were kept fixed. The studies indicated that the phthalate donors would preferentially stabilize the alpha phase of MgCl2, while the alkoxy benzoate donors would stabilize the beta phase more, corroborating experimental results. A comparison of the zip coordination mode with other modes of coordination (mono, chelate, and bridge) indicates that it would be preferred over the mono and chelate coordination modes and be competitive with the bridge coordination mode. The validity of the Fully Fixed Model was then tested by doing calculations with the Partially Relaxed (some of the magnesium and chlorine atoms unfixed) and the Fully Relaxed (all atoms free) Models. The results from the latter two models corrected some of the discrepancies that had been observed for the Fully Fixed Model in comparison to previous experimental and computational investigations but were in general agreement with the Fully Fixed Model, indicating that the overall conclusions drawn with the earlier model are correct. Insertion studies done on an octahedrally coordinated titanium site flanked by two zip-coordinated phthalate donor molecules indicated that the zip-coordinating donors can confer exceptional regioselectivity to the titanium center. A list of potential donors that could serve as external donors, with di-iso-butyl phthalate (DIBP) as the internal donor, was investigated, and it was found that 1,3-diethers would serve as the best external donors to DIBP.

DFT investigation of the potential of porous cages for the catalysis of ammonia borane dehydrogenation - Pal, Amrita; Vanka, Kumar (Chemical Communications, 2011)
Full DFT based quantum mechanical studies reveal that zero dimensional porous structures, especially the newly proposed phosphorus incorporated organic cages, can be excellent catalysts for the dehydrogenation of ammonia borane.

Donor decomposition by lewis acids in Ziegler-Natta catalyst systems: a computational investigation - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (Organometallics, 2014)
The development of new donors (Lewis bases, usually containing oxygen atoms) is one of the chief areas of research in Ziegler-Natta (ZN) olefin polymerization systems. The addition of such donors has led to improvement in the activity and selectivity of ZN systems. However, in order for the donor to be effective, it has to be chemically stable and resistant to decomposition by Lewis acidic species such as AlEt3. Discussed in the current work is the chemical stability of different ester donors, including aromatic benzoate donors and the silyl ester-a promising new donor class in ZN systems. Full quantum chemical calculations with density functional theory (DFT) indicate that esters can undergo decomposition through different pathways upon interaction with species such as the AlEt3 dimer: Al2Et6. Moreover, the studies show that the active, supported titanium catalyst species can cause donor decomposition and, in fact, is likely to be the greater threat to donor decomposition than Al2Et6. This explains why the addition of excess donors can lead to the poisoning of the active site in ZN systems. We have also computationally investigated means of improving the silyl ester donors in order to make them more robust and resilient to donor decomposition by Al2Et6 and the supported active titanium species.

Decoding the morphological diversity in two dimensional crystalline porous polymers by core planarity modulation - Halder, Arjun; Kandambeth, Sharath; Biswal, Bishnu P.; Kaur, Gagandeep; Roy, Neha Chaki; Addicoat, Matthew A.; Salunke, Jagadish K.; Banerjee, Subhrashis; Vanka, Kumar; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul (Angewandte Chemie - International Edition, 2016)

DBU-mediated diastereoselective aldol-type cyanomethylation of isatins - Rao, V. U. Bhaskara; Kumar, Krishna; Das, Tamal; Vanka, Kumar (Journal of Organic Chemistry, 2017)
An efficient, metal-free approach to 3-substituted 3-hydroxybxindole by DBU-mediated highly diastereoselective addition of aryl acetonitrile to N-protected isatin under mild conditions has been developed. The reaction proceeds smoothly to produce respective cyanomethylated adducts in good yield and excellent diastereoselectivity. Further transformation of the cyanide group allowed the synthesis of an advance intermediate of corresponding (+/-) CPC analogue. The mechanistic insight :toward the aldol-type cyanomethylation, of N-tritylisatin with benzyl cyanide was obtained by DFT calculations.

Diastereoselective multi-component tandem condensation: synthesis of 2-amino-4-(2-furanone)-4H-chromene-3-carbonitriles - Gupta, Vijay; Sahu, Debashish; Jain, Shailja; Vanka, Kumar; Singh, Ravi P. (Organic & Biomolecular Chemistry, 2019)
A general strategy for a one-pot stereoselective synthesis of 2-amino-4-(2-furanone)-4H-chromene-3-carbonitriles by reaction of salicylaldehyde, malononitrile and butenolides via a tandem Knoevenagel/Pinner/vinylogous Michael condensation is presented. The beta,gamma-butenolides gave a syn-selective MCR adduct with a dr up to 11.5 : 1. The mechanistic insight into the MCR was obtained by DFT calculations.

Deoxygenative hydroboration of primary and secondary amides: a catalyst-free and solvent-free approach - Kumar, Rohit; Bisai, Milan Kumar; Jain, Shailja; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
In contrast to the recent reports on catalytic hydroboration of amides to amines with pinacolborane (HBpin), a simple catalyst-free and solvent-free method for the hydroboration of a variety of amides has been realized. To get the mechanistic insights, DFT calculations have been performed.

Diverse reactivity of carbenes and silylenes towards fluoropyridines - Kundu, Gargi; Ajithkumar, V. S.; Bisai, Milan Kumar; Tothadi, Srinu; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
The reaction of IDipp with C5F5N led to functionalization of all three carbon atoms of the imidazole ring with HF2- as the counter-anion (1). Reactivity with 2,3,5,6-tetrafluoropyridine gives only C-F bond activation leaving C-H bonds intact (5b). The reaction of SIDipp with C5F5N in the presence of BF3 afforded the ring cleavage product (3). Analogous reactions with silylene led to oxidative addition at the Si(II) center.

Diverse reactivity of hypersilylsilylene with boranes and threecomponent reactions with aldehyde and HBpin - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2021)
The recently reported hypersilylsilylene PhC-(NtBu)(2)SiSi(SiMe3)(3) (1) reacts with BH3, 9-BBN, and PhBCl2 to yield the respective Lewis acid base adducts 2-4, respectively. Compound 4 undergoes isomerization to form a ring expansion product 5. The same silylene was found to initially form an adduct with HBpin (6) and subsequently isomerized to 7 via the rupture of the B-H bond of HBpin (7), where the hydride was bound to the carbon atom of the amidinate ligand and the Bpin unit was attached to the silicon center. Surprisingly, the reaction of 1 with HBcat results in PhC(NtBu)(2)Bcat (8). Subsequently, we have shown that HBcat forms the same product when it reacts with related silylene PhC(NtBu)(2)SiN(SiMe3)(3) (1'). With all of these reactions in hand, we ponder if silylene can activate two small molecules at one time. In this work, we delineate the three-component reactions of silylenes 1 and 1' with 4-fluorobenzaldehyde and HBpin, which afforded unusual coupling products, 9 and 10, respectively. Note that 9 and 10 were prepared from the cleavage of the B-H and C=O bonds by silylene in a single reaction and are the first structurally attested Si-C-O-B coupled products.

Direct (hetero)arylation (DHAP) polymerization of conjugated polymers - new A-B-A monomer design for P(NDI2OD-T2) & the challenges of adopting DHAP for continuous flow processes - Kakde, Navnath R.; Bharathkumar, H. J.; Wavhal, Bhaiyyasaheb A.; Nikam, Arun; Patil, Suneha; Dash, Soumya Ranjan; Vanka, Kumar; Krishnamoorthy, K.; Kulkarni, Amol; Asha, S. K. (Journal of Materials Chemistry C, 2022)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, was synthesized by the atom-economic direct hetero arylation polymerization (DHAP) route using a newly designed A-B-A monomer. The new monomer design involved flanking naphthalene diimide with bithiophene units in the bay position, which was further polymerized with bay substituted 1,4-dibromo naphthalene diimide, to afford the same polymer structure as P(NDI2OD-T2). The new monomer design resulted in a very high molecular weight (M-n: 99.5 kDa, D-M: 2.8) defect-free polymer in a quantitative yield by the DHAP batch process using 1,2,4-trichlorobenzene (TCB) as the solvent. DFT studies revealed that the abstraction of the alpha-proton from the naphthalene diimide substituted 2,2 `-bithiophene was favorable by 2.6 kcal mol(-1) (Delta Delta G) as compared to that from 2,2 `-bithiophene. The reason for this improved C-H activation at the alpha position can be attributed to the presence of C-HMIDLINE HORIZONTAL ELLIPSIS pi stabilizing interactions in naphthalene diimide substituted 2,2 `-bithiophene, which strengthens upon the extended charge delocalization throughout the ring, thus stabilizing the conjugate base generated after the proton abstraction. Continuous flow polymerization was carried out by pumping the DHAP reaction mixture including the monomers, catalyst, and additive (pivalic acid) solubilized in degassed TCB through a pre-heated glass condenser packed with K2CO3 and Celite under aerobic conditions. Reproducible molecular weights of M-n: 29.5 kDa, D-M: 1.7 were obtained at much lower concentrations of reactant mixture compared to that for batch polymerization. This is the first report of the synthesis of P(NDI2OD-T2) by a Continuous Flow Process adopting the DHAP route to obtain a defect-free polymer with reasonable molecular weights. P(NDI2OD-T2) was also synthesized by Stille polymerization as a reference control sample to compare the thermal and charge carrier transport properties of the DHAP polymers. Organic field-effect (OFET) mobility measurements indicated mobility values in the order of 10(-3) cm(2) V-1 s(-1) for the DHAP batch polymer (using the novel monomer design). The P(NDI2OD-T2) synthesized by DHAP batch using the commonly used starting materials - bisbromo naphthalene diimide and bithiophene, exhibited OFET mobilities which were one order less, similar to 10(-4) cm(2) V-1 s(-1). This observation highlights the importance of structural design in the monomer to enhance reactivity and thereby the bulk properties using the DHAP route.

Direct oxidation of bromo-derived Fischer-Borsche oxo-ring using molecular iodine with combined experimental and computational study - Humne, Vivek T.; Ghom, Monica H.; Naykode, Mahavir S.; Dangat, Yuvraj; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2022)
A direct oxidation of the bromo-derived Fischer-Borsche oxo-ring leading to carbazolequinone has been developed by using molecular iodine. This unprecedented transformation has been used for the modular synthesis of the anti-cardiotonic agent murrayaquinone. Furthermore, the present method has been generalized to a broad range of functional groups, with good to excellent yield.

Dual routes toward observation of a trans-H2/hydride complex in an iridium pincer system and hydrogenation catalytic activity - Agrawal, Nisha K.; Dash, Soumya R.; Vanka, Kumar; Jagirdar, Balaji R. (Organometallics, 2023)
The Abstraction of chloride from a six- coordinate complex, trans-[ Ir(H)(Cl)((iPr)4)(POCOP)(PPh3)] (1) [((iPr)4)(POCOP) = 2,6-bis(di-iso-propylphosphinito)benzene,kappa(3)-C6H3-1,3-[OP(Pr-i)(2 )](2)], using NaBAr4f leads to the generation of a dinitrogen complex, trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6). Addition of H-2 to [Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) (6) under extremely mild conditions (1 bar, 298 K) resulted in the reversible coordination of H-2 to generate the cis-[Ir(H)(eta H-2-(2))((iPr)4)(POCOP)(PPh3)](+) (cis-11) complex. The cis-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (cis-11) isomerized to a trans isomer, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11), at 253 K. The isomerization process has been studied and supported by computations. Employing an alternative route, protonation of the trans-[Ir(H)(2)((iPr)4)(POCOP)(PPh3)] complex (2) at 183 K resulted in the formation of an identical, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (trans-11); upon warming the sample, the trans-H-2/hydride complex isomerized to the cis isomer above 253 K. Two independent routes to obtain trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11) species have been established. Reaction of trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6) with C2H4 gave the cis-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complex (cis-15), which also undergoes isomerization to yield an equilibrium mixture of cis/trans-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complexes (cis-15 and trans-15) at 253 K. The trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) complex (6) is an excellent catalyst for hydrogenation of ethylene to ethane under very mild conditions.

Dehydrogenative coupling of alcohols with internal alkynes under nickel catalysis: an access to β-deuterated branched ketones - Subaramanian, Murugan; Gouda, Chandrakant; Roy, Triptesh Kumar; Ganesan, Sivakumar; Banerjee, Subhrashis; Vanka, Kumar; Balaraman, Ekambaram (ACS Catalysis, 2024)
In synthetic organic chemistry, unconventional strategies for advanced chemical synthesis pose interesting and challenging problems. Alcohols act as alkylating agents in the C-C and C-N bond-forming reactions via the dehydrogenative borrowing hydrogen strategy in traditional transition metal catalysis; however, as an acylating agent in the C-C bond-forming reactions is challenging and rarely reported. Here, we report the dehydrogenative coupling of benzylic alcohols with internal alkynes under nickel(II) catalysis, wherein alcohol is used as an acylating agent. This reaction system affords a wide range of alpha-branched aryl ketone derivatives with zero waste generation through the umpolung borrowing hydrogen strategy. Moreover, we have demonstrated the chemodivergent applications of the alpha-disubstituted ketones to other valuable building blocks, including large-scale synthesis of beta-deuterated branched ketones. Several spectroscopic studies, intermediate identification, and density functional theory calculations were performed to elucidate the reaction mechanism.
Keywords: Alcohols; alpha-branched aryl ketones; dehydrogenative coupling; internal alkynes; nickel catalysis; pseudoumpolung

Designing of imine thiophene-ligated metal-complexes and implication in ethylene polymerization - Shaikh, Maulali H.; Ramekar, V. Rohan; Jawoor, Shailaja; Dash, Soumya R.; Birajadar, Rajkumar S.; Pawal, Sandip B.; Thenmani, Nandakumar; Vanka, Kumar; Chikkali, Samir H. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2024)
Polyethylene is the single largest volume polymer produced globally using Ziegler-type catalysts. Numerous modifications have been reported in search of a better catalyst that can control molecular weight, polydispersity, and branching. In our attempts to identify a suitable imine thiophene-ligated chromium complex, we examined 9 different titanium complexes computationally. The DFT investigations considered barriers for insertion, propagation, and termination by beta-H elimination or chain transfer, and identified N-(4-methoxyphenyl)-2-phenyl-1-(thiophen-2-yl)ethan-1-imine(L9) as the most suitable ligand. Subsequently, L9 was prepared in good yield (70%) by condensing 2-phenyl-1-(thiophen-2-yl)ethan-1-one with 4-methoxyaniline. Ligand L9 was treated with early transition metal precursors (Ti, Cr, Zr) to generate a homogenous catalyst. The identity of these catalysts was unambiguously ascertained using a combination of NMR, ICP, FT-IR, UV-Vis spectroscopy, and ESI-MS. The performance of L9-ligated titanium complex [Cat.1] was examined in ethylene polymerization using MMAO as a co-catalyst. Insertion of ethylene was tracked using high-pressure NMR experiments and Cat.1 was found to be active in the polymerization. Ethylene polymerization conditions were optimized to obtain high activity and molecular weight polyethylene. The chromium complex [Cat.2] outperformed the Ti and Zr-derived catalysts with the highest TOF of 6294 mol of PE/mol of Cr/h. Cat.2 produced high molecular weight, high-density polyethylene.
Keywords: Cr-complexes; DFT; high-density polyethylene; Imine thiophene ligand; Polyethylene

Depolymerization of waste polycarbonates to value-added products - Padhi, Ganeshdev; Pansare, Vaibhav Ramachandra; Bajpai, Priyam; Krishna, Gamidi Rama; Vanka, Kumar; Barsu, Nagaraju (ChemSusChem, 2025)
Additive free aminolysis method developed for the depolymerization/upcycling of polycarbonates. We report here chemical recycling of polycarbonate under ambient conditions to get its monomer bisphenol A, monoaminocarbamate and biscarbamates in 1 : 2 : 1 ratio respectively. By employing the secondary amine as the aminating reagent, facilitates the depolymerization to work under additive/catalyst free conditions. The developed method deals with depolymerization of waste polycarbonates and works even with late-stage amine derivatives such as amoxapine and desloratadine which are drugs molecules known to treat neurotic disorders and allergies respectively. The reaction can be scaled up and works with similar efficacy which depicts the efficiency of the depolymerization of wasteend-of-life polycarbonate plastic waste. The biscarbamate and bisphenol-A was further subjected for the post functionalization to obtain amides and phenol in good yields. Developed additive/catalyst free aminolysis of waste polycarbonates to carbamates and monomer BPA at ambient conditions. Variety of secondary amines were screened including the late stage amine derivatives like amoxapine and desloratadine which delivered the expected products successfully. Later the developed methodology was even applied for the different end-of-life polycarbonates with the secondary amine and achieved the depolymerization without any obstacle. Further carried out the scale up reaction and derivatization of carbamates and BPA to amide and phenol synthesis. image
Keywords: Aminolysis; carbamates; depolymerization; End-of-life; Polycarbonate

Double anchoring squaraine dye with triazatruxene amine donor for dye-sensitized solar cells: sequential cosensitization for panchromatic light-harvesting - Ingole, Kiran Balaso; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
Dyes are firmly bound to a semiconducting TiO2 film using carboxylic acid anchoring groups for an efficient electron transfer from the excited state of dye to the conduction band (CB) of TiO2. Strong dye binding can be accomplished with multi-anchoring dye designs to improve photophysical characteristics, including high extinction coefficients, panchromatic absorption, post-sensitization modifications, and dark current suppression, besides enhancing the stability of the dye-TiO2 interface. Herein, a novel KV2D dye with double squaraine acceptor and double carboxylic acid anchoring groups is designed to achieve a high extinction coefficient (epsilon, 3.57 x 105M-1cm-1) and robust binding to the TiO2 film for an effective electron transfer. We systematically changed the amount of coadsorbent chenodeoxycholic acid (CDCA) to control the aggregation of dyes on the TiO2 surface that improves the power conversion efficiency (PCE, eta) for the devices based on the doubleanchoring KV2D. Out of these devices, KV2D: CDCA (1:10) based cell exhibited the best PCE of 5.26% with VOC of 754 mV, JSC of 10.41 mA/cm2, and ff of 67%. The sequential cosensitization studies were carried out with a far-red active dye to find the effect of the strong binding of the sensitizer to the TiO2 film. Interestingly, when di-anchoring, KV2D was sensitized first for 12 h and then sequentially cosensitized with far-red absorbing SQS4 for 5 h to achieve a PCE of 5.0% with VOC of 697 mV, JSC of 10.23 mA/cm2, and ff of 70% with panchromatic spectral response in IPCE upto 730 nm giving higher photocurrent generation.
Keywords: aggregation of dyes; Bulky donor unit; Double acceptor dye; Dye-sensitized solar cells; self-assembly of dye; squaraine dyes; triazatruxene